DESENVOLVIMENTO DE NANOEMULSÃO CONTENDO EUGENOL: PRODUÇÃO, CARACTERIZAÇÃO, VALIDAÇÃO POR CROMATOGRAFIA LÍQUIDA DE ALTA EFICIÊNCIA - Niederauer, Clarissa Denardin (2016)
Currently the demand for aesthetic treatments has increased considerably, but often cause pain and, because of this, are used topical anesthetic prior to treatment. Because of this, the search to an agent with these characteristics is permanent, in view of the difficulty in obtaining an agent having these characteristics related to the diffusion of the drug and adequate distribution on the skin. The eugenol, the main compound of the ethanol extract of clove cloves (syzygium aromaticum), is responsible for much of the pharmacologic effects attributed to plant, including the anesthetic activity. With the purpose of obtaining a product that complies fully with the anesthetic effect topically without cause systemic adverse effect, the objective of this work was the prodution, characterization and hplc assay of a nanoemulsion containing eugenol. In the production of the nanoemulsion, the parameters evaluated were: mechanical agitation at speeds of 10,000, 20,000 and 26,000 rpm, 7.5 and 15 minutes stirring time and the active concentration of 0.50; 0.75 and 1.00%. The characterizations of the formulations were the average droplet diameter, polydispersity index, zeta potential and ph, as well as the determination of the active was performed via liquid chromatography high performance (hplc). Stability studies were performed on a 75 day period in three temperature conditions (5, 25 and 40 ° c). Best results were obtained when we used mechanical stirring with 20,000 rpm for 7.5 minutes stirring time and the concentration of 1.00% active, producing nanoemulsions having an average diameter droplet 101.17 ± 6.80 nm index a polydispersity 0.135 ± 0.027, zeta potential of -7.19 ± 0.713 and pH 4.84 ± 0.04. This formulation was stable for up to 30 days, keeping the results as stored at 5 and 25ºc. As for the determination of recoveries 72 to 106% of the assets were obtained. Thus, it is concluded that the methodology used is feasible for production nanoemulsions containing eugenol.